Forecasting stock markets using machine learning : forecasting the PSI-20 index using a machine learning approach - Dinis Oliveira, André (2017)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management